Heat shielding part for vehicle, heat shielding film, and manufacturing method for heat shielding part for vehicle
A heat shielding film with a high-hardness inorganic compound layer and optional alumite layer, formed via ultraviolet irradiation, addresses peeling and dimensional issues, enhancing durability and fuel efficiency in engine pistons.
Patent Information
- Application Number
- JP2020206263
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-11
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Existing heat shielding films for vehicle components, particularly those used on engine pistons, suffer from peeling and lack of mechanical strength in high-temperature environments, leading to dimensional changes and loss of fuel efficiency due to insufficient heat resistance and thermal expansion.
A heat shielding film composed of an inorganic compound layer with scale-like inorganic particles dispersed in an alkoxide-based compound, having a Vickers hardness of 50 to 100 HV, and optionally an alumite layer below, is formed using ultraviolet irradiation to maintain dimensional accuracy and prevent peeling.
The film provides enhanced heat shielding without peeling, maintains dimensional stability, and prevents thermal deformation, ensuring improved fuel efficiency and durability in harsh engine conditions.
Smart Images

Figure 0007605429000003 
Figure 0007605429000004 
Figure 0007605429000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a vehicle heat-shielding part, which is a part for a vehicle to which heat-shielding properties have been imparted by the formation of a heat-shielding film, and the heat-shielding film formed on the vehicle heat-shielding part, as well as a method for manufacturing the vehicle heat-shielding part.The present invention also relates to a vehicle part that requires heat-shielding properties (referred to as a "part to be heat-shielded" in this specification), for example, a vehicle heat-shielding part formed by forming a heat-shielding film on the top surface of an engine piston, the heat-shielding film, and a method for manufacturing the vehicle heat-shielding part. [Background technology]
[0002] In order to improve fuel efficiency, etc., a heat insulating film is formed on the top surface of the piston to reduce the heat loss caused by the heat generated in the combustion chamber of the engine being released through the piston, etc., thereby improving thermal efficiency.
[0003] As such a heat shielding film, Patent Document 1 listed below describes a configuration in which a heat shielding film is formed on the top surface of the piston, which comprises an insulating layer made of resin with hollow particles embedded therein, and an inorganic coating layer made of inorganic materials such as silica, zirconia, alumina, and ceria containing hollow particles formed on the surface of this insulating layer.
[0004] Furthermore, in view of the fact that the resin insulating layer and the inorganic coating layer containing hollow particles provided in the heat shielding film described in Patent Document 1 above do not have sufficient heat resistance in high-temperature environments such as the combustion chamber of an engine, and are prone to peeling due to the generation of cracks in the inorganic coating layer, Patent Document 2 listed below further proposes forming the insulating layer on the top surface of the piston using an anodized aluminum layer, and forming an inorganic compound layer on this insulating layer (anodized aluminum layer) consisting of scale-like inorganic particles dispersed in an inorganic compound formed from an alkoxide, thereby forming a heat shielding film consisting of the aforementioned anodized aluminum layer and inorganic compound layer (Figures 10 and 11 of Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6067712 [Patent Document 2] Patent No. 6339118 Summary of the Invention [Problem to be solved by the invention]
[0006] In the heat shielding film described in Patent Document 2 cited above, the insulating layer formed from resin and hollow particles in Patent Document 1 is changed to an anodized layer, and the inorganic coating layer formed from hollow particles and inorganic material in Patent Document 1 is changed to an inorganic compound layer in which scale-like inorganic particles are dispersed in an inorganic compound formed from an alkoxide, thereby overcoming the drawback of low heat resistance, which was a weakness of the heat shielding film described in Patent Document 1.
[0007] However, when a "real-world engine test" was conducted in which a piston having the heat-shielding film described in Patent Document 2 formed on its top surface was mounted on an engine and operated, it was confirmed that part of the heat-shielding film had peeled off, and it was determined that the heat-shielding film did not have the mechanical strength required for a heat-shielding film to be formed on the top surface of an engine piston.
[0008] In particular, in a unit test in which the aforementioned inorganic compound layer containing dispersed scale-like inorganic particles was formed alone and conducted in an environment simulating an engine, it was confirmed that peeling and other problems became prominent when the thickness of the inorganic compound layer exceeded 40 μm. As a result, it has become impossible to adopt a configuration in which the thickness of the inorganic compound layer is increased so that a single layer functions as a heat shielding film, thereby omitting the insulating layer provided underneath.
[0009] Here, when attempting to increase the hardness of the inorganic compound formed using the alkoxide as a starting material, it is conceivable to increase the firing temperature of the inorganic compound layer.
[0010] However, when forming a heat-shielding film for parts to be heat-shielded, such as aluminum alloy pistons, if the inorganic compound layer is sintered at a high sintering temperature, the parts to be heat-shielded may experience not only temporary changes in external dimensions due to thermal expansion caused by the heating during sintering, but also permanent changes in external dimensions due to the release of residual stress, etc. Therefore, as an example, if the part to be heat-shielded is a piston, the size of the piston may not be as designed, and the clearance with the cylinder bore may change.
[0011] For this reason, it is desirable to perform the firing at as low a temperature as possible, and it is not possible to adopt a configuration in which the hardness of the protective layer is increased by raising the firing temperature.
[0012] Furthermore, in the embodiment of Patent Document 2, a configuration is adopted in which an oxalic acid anodized aluminum layer, which is an insulating layer, is formed by anodizing using an oxalic acid bath. However, this oxalic acid anodized aluminum is brittle due to its high porosity, and it has been confirmed that damage to the coating occurs in actual testing of a single-cylinder engine in which only the anodized aluminum layer is formed. As a result, if the inorganic compound layer peels off, the anodized aluminum layer formed underneath will also peel off, completely losing the effects of the heat-shielding film, such as improving fuel efficiency.
[0013] Therefore, the present invention has been made to eliminate the above-mentioned drawbacks of the conventional technology, and aims to provide a heat-shielding film that will not peel off even when installed in harsh environments such as inside the combustion chamber of an engine, and a method for forming such a heat-shielding film. [Means for solving the problem]
[0014] The means for solving the problems are described below together with the reference numerals used in the description of the embodiment of the invention. The reference numerals are used to clarify the correspondence between the description of the claims and the description of the embodiment of the invention, and needless to say, are not used to restrict the interpretation of the technical scope of the present invention.
[0015] In order to achieve the above object, the heat shield part for a vehicle of the present invention comprises: In a heat shielding part for a vehicle, at least a part of the surface of a heat shielding target part 2 is covered with a heat shielding film 1, The heat insulating film 1 includes at least an inorganic compound layer 10 formed by dispersing one or more types of scale-like inorganic particles 12 selected from the group consisting of mica, talc, and wollastonite in an inorganic compound 11 formed from an alkoxide, The inorganic compound layer 10 has a Vickers hardness (HV) of 50 to 100. the law of nature, The heat-shielding target part maintains its outer dimensions before the heat-shielding film is formed. The present invention is characterized by the above (Claim 1). In this way, the vehicle heat-shielding part of the present invention has a relatively high hardness of HV50 to 100, while the heat-shielding part 2 maintains the external dimensions before the heat-shielding film 1 was formed without undergoing permanent thermal deformation, and thus differs from known vehicle heat-shielding parts in which the hardness is increased by firing an inorganic compound layer in a high-temperature atmospheric furnace.
[0016] The Young's modulus of the inorganic compound layer 10 can be set to 12 to 25 GPa (claim 2).
[0017] The heat shielding film 1 may further include an anodized aluminum layer 20 below the inorganic compound layer 10 (claim 3).
[0018] In this case, it is preferable that the anodized aluminum layer 20 is a sulfate anodized aluminum layer (claim 4).
[0019] The inorganic compound layer 10 may have a thickness of 10 to 200 μm (claim 5).
[0020] Moreover, the thickness of the heat shielding film 1 can be set to 10 to 400 μm (claim 6).
[0022] The alkoxide may be a mixture of 30 to 100% by mass of a tetrafunctional alkoxide and 0 to 70% by mass of a difunctional or trifunctional alkoxide (see claims). 7 ).
[0023] The heat-shielded part 2 may be an engine piston (see claim 8 ).
[0024] In addition, the heat shielding film 1 of the present invention is A heat shielding film 1 is formed on at least a part of the surface of a heat shielding target part 2 and constitutes a heat shielding target part for a vehicle together with the heat shielding target part 2, The inorganic compound layer 10 is formed by dispersing one or more kinds of scale-like inorganic particles 12 selected from the group consisting of mica, talc, and wollastonite in an inorganic compound 11 formed from an alkoxide, and has a Vickers hardness (HV) of 50 to 100. The film is formed on the surface of the heat-shielding target part 2, which maintains its outer dimensions before the film formation. The present invention is characterized by the following features (claim 9 ).
[0025] An anodized aluminum layer 20 may be provided under the inorganic compound layer 10 (see claims). 10 ).
[0026] In this case, the thickness of the anodized aluminum layer can be set to 10 to 200 μm (see claims). 11 ).
[0027] The thickness of the inorganic compound layer 10 can be set to 10 to 200 μm (see claims). 12 ).
[0029] Furthermore, the method for manufacturing a heat shielding part for a vehicle of the present invention includes the steps of: A method for manufacturing a heat shielding part for a vehicle, comprising covering at least a part of a surface of a heat shielding target part (2) with a heat shielding film (1), The heat shielding film 1 includes at least an inorganic compound layer 10 in which one or more types of scale-like inorganic particles 12 selected from the group consisting of mica, talc, and wollastonite are dispersed, The inorganic compound layer 10 is A paint production process for producing a paint comprising an alkoxide solution in which the scale-like inorganic particles 12 are dispersed; A coating film forming process in which the paint is applied to the surface of the heat-shielding target part 2 to form a coating film; The coating film is irradiated with light having a wavelength of 500 nm or less, preferably in the ultraviolet range (200 to 400 nm). The temperature rise of the heat-shielding target parts is suppressed while keeping the hardness at 50 to 100 on the Vickers hardness scale (HV). The method is characterized in that the material is formed through a firing process (claim 13 ).
[0030] In the method for producing a heat shielding part for a vehicle, the alkoxide may be a mixture of 30 to 100 mass % of a tetrafunctional alkoxide and 0 to 70 mass % of a difunctional and / or trifunctional alkoxide (see claims 1 and 2). 14 ).
[0031] The heat shielding film 1 may include an alumite layer 20, The coating film forming step may be performed on the surface of the heat shielding target part 2 made of aluminum or an aluminum alloy on which an anodized aluminum layer 20 is formed (see claim 15 ).
[0032] In this case, it is preferable to form the alumite layer 20 by anodizing using a sulfuric acid bath (see claims). 16 ).
[0033] Furthermore, the heat-shielded part 2 may be a piston for an engine (see claim 17 ). Effect of the Invention
[0034] With the above-described configuration of the present invention, the vehicle heat shielding part and heat shielding film 1 of the present invention can provide the following remarkable effects.
[0035] By making the inorganic compound layer 10 have a relatively high Vickers hardness (HV) of 50 to 100, it is possible to make the inorganic compound layer 10 less susceptible to peeling, even if the film thickness is increased.Increasing the film thickness of the inorganic compound layer 10 to improve the heat insulation properties makes it possible for the inorganic compound layer 10 alone to function as a heat insulation film, without forming an insulating layer such as an anodized layer 20 underneath.
[0036] However, this does not negate the adoption of a configuration in which, in the heat-shielding film 1 of the present application, an anodized aluminum layer 20 is provided below the inorganic compound layer 10, or another insulating layer (not shown) is provided in place of the anodized aluminum layer 20 or in addition to the anodized aluminum layer 20.
[0037] Furthermore, by setting the Young's modulus of the inorganic compound layer 10 to 12 to 25 GPa, it is possible to impart flexibility to the inorganic compound layer 10.
[0038] By imparting flexibility to the inorganic compound layer 10 in this manner, it is possible to impart properties that make the inorganic compound layer 10 less susceptible to cracking, thereby providing a heat shielding film 1 that is even less susceptible to peeling and the like.
[0039] In the heat shielding film 1 further comprising the alumite layer 20 below the inorganic compound layer 10, the heat insulating effect of the alumite layer 20 makes it possible to obtain a heat shielding film 1 with a higher heat shielding effect.
[0040] In particular, when the anodized aluminum layer 20 is a sulfate anodized aluminum layer formed by anodizing using a sulfuric acid bath, it is possible to form an anodized aluminum layer 20 that is high in density and hardness compared to when the anodized aluminum layer is formed using oxalic acid anodized aluminum.
[0041] Furthermore, while the heat-shielding part for vehicles of the present invention has a relatively high hardness of HV50 to 100, the part 2 to be heat-shielded maintains its outer dimensions from before the heat-shielding film 1 was formed without any permanent change in outer dimensions. Therefore, even if the part 2 to be heat-shielded is, for example, an engine piston, the clearance with the engine cylinder bore can be maintained approximately as designed.
[0042] Furthermore, in the manufacturing method of the vehicle heat-shielding part of the present invention, the coating is baked in the baking process by irradiating it with light having a wavelength of 500 nm or less, preferably in the ultraviolet range (200 to 400 nm), thereby making it possible to bake the inorganic compound 11 constituting the inorganic compound layer 10 to a high hardness while maintaining the temperature of the part 2 to be heat-shielded at a relatively low temperature.
[0043] As a result, even for heat-insulating parts 2, such as aluminum alloy pistons used in engines, whose dimensions become distorted due to thermal expansion when heated to high temperatures, it is possible to form a high-hardness inorganic compound layer 10 while maintaining dimensional accuracy.
[0044] Furthermore, as described above, by being able to keep the temperature of the heat-shielding part 2 low, even when the heat-shielding film 1 is formed on the heat-shielding part 2 which has been forged, heat treated, or otherwise imparted with a microcrystalline structure or residual stress, it is possible to form a high-hardness inorganic compound layer 10 while maintaining the microcrystalline structure and residual stress possessed by the heat of the firing process without causing them to be lost. [Brief description of the drawings]
[0045] [Figure 1] FIG. 2 is an explanatory diagram of a heat shielding part for a vehicle having a heat shielding film (single layer structure) of the present invention. [Diagram 2] FIG. 2 is an explanatory diagram of a heat shielding part for a vehicle having a heat shielding film (two-layer structure) of the present invention. [Diagram 3] FIG. 4 is an explanatory diagram of a film forming process of an inorganic compound layer. [Figure 4] Graph showing change in hydrolysis reaction rate with respect to change in pH of alkoxide (Si alkoxide). [Diagram 5] 1 is a graph showing the change in light transmittance of an alkoxide paint with respect to the change in wavelength of irradiated light. [Figure 6] 1 is a graph showing the change in reflectance of an alkoxide paint with respect to the change in wavelength of irradiated light. [Figure 7] 1 is a graph showing the change in light absorptance of an alkoxide paint relative to the change in wavelength of irradiated light. [Figure 8] FT-IR spectrum of the inorganic compound of Example 1 (calcined by UV irradiation for a specified time). [Figure 9] FT-IR spectrum of the inorganic compound of Example 2 [baked by UV irradiation for a specified time (short time) shorter than that of Example 1]. [Figure 10] FT-IR spectra of the inorganic compounds of Comparative Example 1 (calcined in a low-temperature atmospheric furnace) and Comparative Example 2 (calcined in a high-temperature atmospheric furnace). [Figure 11] FT-IR spectra of the inorganic compounds of Example 2 (calcined by short-term ultraviolet irradiation) and Comparative Example 1 (calcined in a low-temperature atmospheric furnace). [Figure 12]1 is a graph comparing the hardness (HV) of inorganic compounds in Example 2 (fired by short-time ultraviolet irradiation) and Comparative Example 1 (fired in a low-temperature atmospheric furnace). [Figure 13] Differential thermal analysis (TG-DTA) graph of a sample that has not been pH adjusted. [Figure 14] Differential thermal analysis (TG-DTA) graph of the sample after pH adjustment. [Figure 15] Graph showing the change in hardness of inorganic compounds fired in an atmospheric furnace with or without pH adjustment. [Figure 16] 1 is a graph showing the change in hardness of an inorganic compound calcined by ultraviolet irradiation with or without pH adjustment. [Figure 17] Graph showing the change in hardness of inorganic compounds due to the addition of amines (pH adjustment). [Figure 18] 3 is a graph showing the change in Young's modulus of an inorganic compound with respect to the change in the functional group content. [Figure 19] 1 is a graph showing the change in hardness (HV) of inorganic compounds with trifunctional group contents of 0%, 17%, 33%, and 50% by mass relative to the change in amine content (pH adjustment). [Figure 20] FIG. 1 is an explanatory diagram of the test apparatus used in the hydropulse test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0046] Next, an embodiment of the present invention will be described below with reference to the accompanying drawings.
[0047] [Overall structure of heat shielding part and heat shielding film for vehicle] As shown in Figures 1 and 2, the heat-shielding part for a vehicle of the present invention comprises a heat-shielding part 2 which is a metallic vehicle part such as an engine piston, and a heat-shielding film 1 formed on at least a portion of the surface of the heat-shielding part 2, for example the top surface in the case of the aforementioned piston, to impart heat-shielding properties.
[0048] As shown in Figures 1 and 2, this heat-shielding film 1 is a film formed on the surface of the part 2 to be heat-shielded in order to block thermal conduction to the part 2, and includes at least an inorganic compound layer 10 consisting of an inorganic compound 11 formed from an alkoxide in which scale-like inorganic particles 12 are dispersed.
[0049] The heat-shielding film 1 in Figure 1 is a heat-shielding film 1 formed from a single layer of the inorganic compound layer 10 described above, while Figure 2 shows a heat-shielding film 1 formed from two layers, that is, the inorganic compound layer 10 and an anodized layer 20 formed under this inorganic compound layer 10.
[0050] As shown in FIG. 1, when the heat shielding film 1 is formed of a single inorganic compound layer 10, the thickness of the heat shielding film is, for example, 10 to 200 μm.
[0051] Furthermore, in the case of a two-layer structure of an inorganic compound layer 10 and an anodized aluminum layer 20 as shown in FIG. 2, the part 2 to be heat-shielded is made of aluminum or an aluminum alloy, and the part 2 to be heat-shielded is anodized in advance to form the anodized aluminum layer 20, and the inorganic compound layer 10 described above is then formed on the anodized aluminum layer 20.
[0052] In this way, when the heat shielding film 1 has a two-layer structure of an inorganic compound layer 10 and an anodized aluminum layer 20, as an example, the total thickness of the heat shielding film 1 is 20 to 400 μm, of which the thickness of the inorganic compound layer is 10 to 200 μm and the thickness of the anodized aluminum layer is 10 to 200 μm.
[0053] The heat shielding film 1 of the present invention is not limited to the configuration shown in Figures 1 and 2, and may have a configuration in which, in place of the anodized aluminum layer 20 in the heat shielding film 1 of the configuration shown in Figure 2, a known insulating layer, such as an insulating layer made of an inorganic material in which hollow particles are dispersed, is provided, or a known insulating layer, such as an insulating layer made of an inorganic material in which hollow particles are dispersed as described above, is provided between the anodized aluminum layer 20 and the inorganic compound layer 10 in Figure 2.Various configurations can be adopted as long as they include at least the inorganic compound layer 10 described above.
[0054] [Inorganic compound layer] Of the layers constituting the heat shielding film 1 of the present invention, the aforementioned inorganic compound layer 10, as described above, has a structure in which scale-like inorganic particles 12 are dispersed in inorganic compound 11 formed from alkoxide, and has a relatively high hardness of 50 to 100 in Vickers hardness (HV).As shown in Figures 1 and 2, the inorganic compound layer 10 has a structure in which scale-like inorganic particles 12 are arranged with their longitudinal direction parallel to the surface of the component to be heat shielded and are bonded together with inorganic compound 11 formed from alkoxide as a binder.
[0055] The aforementioned scale-like inorganic particles 12 dispersed in the inorganic compound layer 10 may include mica, talc, and wollastonite, which may be used alone or in combination of multiple types.
[0056] Here, "scale-like" refers to a shape in which the thickness is sufficiently small compared to the length, and in addition to plate-like and flake-like shapes, fibrous and needle-like shapes are also included in the term "scale-like" as long as the thickness is sufficiently small compared to the length.
[0057] The size of the scale-like inorganic particles 12 dispersed in the inorganic compound layer 10 is preferably about 1 to 500 μm, and more preferably about 1 to 50 μm, in average length.
[0058] Such scaly inorganic particles 12 are dispersed in the inorganic compound layer 10 at a mass ratio of 20 to 70%.
[0059] The inorganic compound 11, which is the other material constituting the inorganic compound layer 10 described above, is a metal oxide formed by a sol-gel method using an alkoxide as a starting material.
[0060] The alkoxide used as the starting material is a compound in which the hydrogen (H) of the hydroxyl group (-OH) of alcohols is replaced with a metal, and the sol-gel method described above is a process that uses this alkoxide as the starting material, passing through a sol and gel state through hydrolysis reactions and polycondensation reactions, and finally synthesizing a metal oxide.
[0061] As the metal for this alkoxide, various metals can be used as long as they are capable of producing metal oxides by the sol-gel method described above. As an example, alkoxides of metals such as silicon (Si), zirconium (Zr), titanium (Ti), aluminum (Al), cerium (Ce), and B (boron) can be used. Of these, silicon (Si) and zirconium (Zr) are particularly desirable because they are highly hard and relatively inexpensive to obtain.
[0062] These alkoxides may be used alone, or a mixture of a plurality of types of alkoxides may be used.
[0063] In order to obtain an inorganic compound layer 10 with high hardness, it is preferable to use an alkoxide having four functional groups, such as tetramethoxysilane, tetraethoxysilane, or tetrapropoxysilane, as the starting material, and it is also possible to use an alkoxide having four functional groups alone.
[0064] However, when an alkoxide with four functional groups is used alone, the inorganic compound layer 10 has high hardness and a high Young's modulus. However, since the high Young's modulus makes the inorganic compound layer 10 difficult to deform, cracks may easily occur during use depending on the application and the material of the part 2 to be heat-shielded.
[0065] Therefore, in order to impart hardness to the inorganic compound layer 10 while lowering the Young's modulus and imparting flexibility, it is preferable to use an alkoxide based on a tetrafunctional alkoxide to which is added a portion of a trifunctional and / or difunctional alkoxide.
[0066] R as trifunctional alkoxide 1 M(OR 2 )3,2-functional alkoxide R 1 2M(OR 2 Various alkoxides represented by the formula 2 can be used, where "M" is a metal such as Si, Ti, Zr, Al, or B, and "R 1 " is a monovalent organic group, specifically an alkyl group, an alkenyl group, an alkynyl group, an aryl group, etc.2 " is an alkyl group having 1 to 4 carbon atoms, and specific examples thereof include a methoxy group, an ethoxy group, and a propoxy group.
[0067] Examples of such alkoxides of three functional groups include methyltrippropoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, isopropyltrimethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, propyltriethoxysilane, isopropyltriethoxysilane, butyltriethoxysilane, isobutyltriethoxysilane, ethyltrippropoxysilane, methyltriisopropoxysilane, and ethyltriisopropoxysilane.
[0068] Examples of alkoxides having two functional groups include dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldipropoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, diethyldipropoxysilane, dipropyldimethoxysilane, dipropyldiethoxysilane, and dipropyldipropoxysilane.
[0069] As an example of an alkoxide having a mixture of alkoxides having different numbers of functional groups, a mixture of 30 to 90 mass% of an alkoxide having 4 functional groups and 10 to 70 mass% of an alkoxide having 2 functional groups and / or 3 functional groups can be used.
[0070] FIG. 3 shows an example of a method for forming an inorganic compound layer 10 by a sol-gel method using an alkoxide as a starting material.
[0071] The formation of the inorganic compound layer 10 by the sol-gel method involves first preparing a raw material liquid by mixing an alkoxide with a solvent, and then producing a paint (hereinafter referred to as "alkoxide paint") in which the aforementioned scale-like inorganic particles 12 are dispersed in this raw material liquid (paint production process).
[0072] Since the alkoxy group is hydrophobic, the solvent used is a lower alcohol having hydrophilic and hydrophobic characteristics, such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, or isobutyl alcohol.
[0073] In the example shown in Figure 3, the scale-like inorganic particles 12 are added at the same time as the alkoxide and solvent are mixed, but instead of this configuration, the alkoxide and solvent may be mixed to obtain a raw material liquid (sol), and the scaly inorganic particles 12 may be added to this raw material liquid and stirred and dispersed to produce the alkoxide paint, or the scaly inorganic particles 12 may be mixed in advance with either the alkoxide or the solvent, and then these may be mixed.
[0074] Next, the paint produced in the above process is applied to the surface of the part 2 to be heat-shielded by a known method such as spin coating, dip coating, spray coating, etc., to form a coating film (coating film formation process).
[0075] The coating film formed on the surface of the part 2 to be heat-shielded is pre-baked in an atmospheric furnace or the like as necessary (pre-baking step).
[0076] Thereafter, the coating film is baked by irradiation with light (electromagnetic waves) (baking step), forming an inorganic compound layer 10 in which scale-like inorganic particles are dispersed in an inorganic compound made of metal oxide.
[0077] The experimental results described below have confirmed that the aforementioned coating film is most susceptible to absorbing light with wavelengths of 500 nm or less, and more preferably, light in the ultraviolet range (200 to 400 nm). The aforementioned baking process is carried out by irradiating the coating with ultraviolet light using a metal halide lamp or the like as a light source.
[0078] When using a metal halide lamp as the light source, the irradiation conditions are, for example, a light source heat output of 2 to 4 kW and a peak illuminance of 700 to 1800 mW / cm. 2 It is.
[0079] It is preferable to add a pH adjuster to the above-mentioned paint to adjust the pH to a more alkaline pH than before adjustment, preferably a more alkaline pH than before adjustment and a pH of 9.5 or higher, or to a pH of 4 or lower. When adjusting to a pH of 4 or lower (acidic), examples of such pH adjusters that can be used include inorganic acids (hydrochloric acid, phosphoric acid), organic acids (acetic acid, citric acid, oxalic acid), and carboxylic acid anhydrides (phthalic anhydride, maleic anhydride). Also, when adjusting to a more alkaline pH than before adjustment, examples of the pH adjuster that can be used include amines (m-xylylenediamine, triethylamine), and ammonia.
[0080] FIG. 4 shows the change in the hydrolysis reaction rate with respect to the pH of the raw material liquid (sol) obtained by mixing alkoxide and a solvent.
[0081] As shown in Figure 4, by adding a pH adjuster, the pH of the paint (raw material liquid) can be shifted to the acidic or alkaline side, thereby significantly improving the hydrolysis reaction rate of the paint, thereby improving the reactivity during pre-baking and baking, shortening the pre-baking time and baking time, and increasing the hardness of the resulting inorganic compound layer 10.
[0082] [Anodized aluminum layer] The heat-shielding film 1 of the present invention may be constructed of a single layer of the inorganic compound layer 10 described above, as shown in Figure 1, but when the part 2 to be heat-shielded is made of aluminum or an aluminum alloy, the heat-shielding film 1 may be formed as a two-layer structure having an anodized layer 20 below the inorganic compound layer 10, as explained with reference to Figure 2.
[0083] This anodized aluminum layer 20 is formed in advance by anodizing on the surface of the aluminum or aluminum alloy part 2 to be heat-shielded, before the inorganic compound layer 10 is formed.
[0084] For such anodized aluminum layer 20, either an oxalic acid anodized aluminum layer formed by anodization using an oxalic acid bath, or a sulfate anodized aluminum layer formed by anodization using a sulfuric acid bath can be used.
[0085] However, since the hardness of the anodized aluminum layer 10 formed in a sulfuric acid bath is higher (HV150 or more) than the hardness of the anodized aluminum layer 10 formed in an oxalic acid bath (HV70 to 90), it is preferable to use a sulfate anodized aluminum layer formed in a sulfuric acid bath.
[0086] [Parts to be heat-shielded] The heat shielding film 1 of the present invention described above is formed on the part 2 to be heat shielded, which is a metal part for a vehicle such as an engine piston, as described above.
[0087] According to the above-mentioned method for forming a heat shielding film, a high-hardness heat shielding film 1 (inorganic compound layer 10) can be formed on the surface while suppressing a temperature rise of the part 2 to be heat shielded, and therefore it is possible to prevent permanent dimensional changes caused by the release of residual stresses that can occur when the part 2 to be heat shielded is heated to high temperatures during sintering. In particular, even when forming on products made of aluminum or aluminum alloys that can suffer relatively large dimensional errors due to heating, or products that have a microcrystalline structure by forging or heat treatment, it is possible to obtain an inorganic compound layer 10 with a relatively high hardness of HV50 to 100 while maintaining the dimensional accuracy before the formation of the heat shielding film 1, and it is possible to suppress changes in the internal structure of the part 2 to be heat shielded that are caused by the growth of crystal grains, and this method is suitable for forming a heat shielding film on a part 2 to be heat shielded that is, for example, an aluminum alloy piston for an engine. EXAMPLES
[0088] Next, the results of the tests carried out to determine the optimum conditions for forming the heat shielding film of the present invention, as well as the results of fatigue tests and durability tests of the heat shielding film formed by the method of the present invention will be described below.
[0089] [Confirmation of the optimal wavelength of irradiation light used in the firing process] (1) Purpose and focus of the experiment The purpose of this experiment is to determine the wavelength range of light that is highly absorbed by the coating film of alkoxide paint.
[0090] In the conventional method of baking a coating in an atmospheric furnace, the heat-shielded part 2 on which the coating has been formed is placed into the atmospheric furnace for baking. Therefore, an increase in the baking temperature (temperature inside the furnace) would increase the temperature of not only the coating but also the heat-shielded part 2, which could cause permanent changes to the dimensions of the heat-shielded part 2, and therefore the baking temperature could not be increased, and therefore the hardness of the resulting inorganic compound layer 10 was low.
[0091] In order to solve the above problems and obtain an inorganic compound layer 10 with a relatively high hardness of HV50 to 100 while maintaining the dimensional accuracy of the heat-shielding part 2 before and after the formation of the inorganic compound layer 10, a new firing method is required that can pinpoint heat only on the coating film while suppressing the temperature rise of the heat-shielding part 2.
[0092] As for such a baking method, the inventors of the present invention hypothesized that by irradiating the coating with light of a wavelength that is highly absorbed by the coating, it would be possible to selectively heat only the coating while suppressing the temperature rise of the part 2 to be heat-shielded.As a first step in exploring the feasibility of baking using this method, they conducted this experiment to determine the wavelength of light that is highly absorbed by the coating of an alkoxide paint.
[0093] (2) Experimental Method Samples were created by applying an alkoxide paint containing mica as scaly inorganic particles to a borosilicate glass substrate at thicknesses of 11 μm, 21 μm, 40 μm, and 60 μm. Each sample was irradiated with light with wavelengths of 260 to 2200 nm, and the changes in light transmittance, reflectance, and absorptance with respect to the change in wavelength were measured.
[0094] (3) Experimental results Of the above tests, the change in transmittance of each sample when irradiated with light having a wavelength of 260 to 2200 nm is shown in Figure 5, and the change in reflectance is shown in Figure 6.
[0095] The absorptivity of the samples with a coating film of 40 μm thickness is shown in FIG.
[0096] (4) Discussion As shown in Figures 5 and 6, for samples with coatings of any thickness, a rapid decrease in both transmittance and reflectance was observed at wavelengths of 500 nm or less, and it was confirmed that both transmittance and reflectance decreased as the wavelength became shorter.
[0097] Here, the light absorbed by the coating is the total irradiated light minus the transmitted and reflected light. Therefore, the above results show that for all samples, in the range of wavelengths below 500 nm, the shorter the wavelength, the higher the light absorption rate. This confirms that irradiating light with a wavelength of 500 nm or less is effective in suppressing the temperature rise of the heat-shielded part 2 and heating the coating in a pinpoint manner.
[0098] Furthermore, Figure 7, which shows the absorptance of the sample with a coating film of 40 μm thickness, shows that the absorptance plateaus when it exceeds 70% at a wavelength of 285 nm, and this phenomenon was observed not only for the sample with a coating film of 40 μm thickness, but also for samples with other coating thicknesses.
[0099] Therefore, it was confirmed that irradiation with light in the ultraviolet range (200 to 400 nm), and more preferably with light with a wavelength of 285 nm or less, makes it possible to maximize the temperature increase of the coating film while minimizing the temperature increase of the components to be heat-shielded.
[0100] In addition, when irradiating light with a wavelength exceeding 500 nm, the transmittance and reflectance are high and the light is not absorbed by the coating, so the heating effect is thought to be low.
[0101] [Confirmation of the effect of baking by ultraviolet irradiation] (1) Purpose of the study In the aforementioned optimum wavelength confirmation test, it was confirmed that the coating film has a high absorption rate due to irradiation with light of wavelengths of 500 nm or less, and by baking the coating film, it was confirmed that the reaction of the obtained inorganic compound is promoted (no residual hydroxyl groups are found) and the hardness is increased.
[0102] (2) Test method As examples, a raw material liquid, which is a mixture of silicon alkoxide with four functional groups and a solvent (no scaly inorganic particles or pH adjuster added), was irradiated with ultraviolet light for a specified period of time using a metal halide light source (wavelength 200 to 400 nm; output 80 W / cm) at an irradiation distance of 440 mm, and then baked to obtain an inorganic compound (silica compound) (Example 1), and an inorganic compound was obtained by irradiating the same raw material liquid with ultraviolet light for a shorter period of time (shorter period) than Example 1 using a metal halide light source at an irradiation distance of 245 mm, and then baking the same (Example 2).
[0103] As comparative examples, an inorganic compound was prepared by firing a similar raw material liquid in an atmospheric furnace at a low temperature (a temperature that does not cause a permanent change in the external dimensions of the part to be heat-shielded) (Comparative Example 1), and an inorganic compound was prepared by firing in an atmospheric furnace at a high temperature (a temperature that causes a permanent change in the external dimensions of the part to be heat-shielded) (Comparative Example 2).
[0104] The progress of the reaction was confirmed for the inorganic compounds of Examples 1 and 2 and Comparative Examples 1 and 2 by using Fourier transform infrared spectroscopy (FT-IR method).
[0105] The progress of the reaction was evaluated as "reaction complete" when the Si-O stretching vibration was confirmed from the spectrum shape but the Si-OH stretching vibration was not confirmed, and otherwise it was evaluated as "reaction incomplete."
[0106] In addition, the hardness (HV) of each sample after firing was measured.
[0107] (3) Test results The FT-IR spectra of the inorganic compounds of Examples 1 and 2 that were calcined by ultraviolet irradiation are shown in FIGS. 8 and 9, respectively.
[0108] Figure 10 shows side-by-side FT-IR spectra of the inorganic compound of Comparative Example 1 (low-temperature calcined) calcined in an atmospheric furnace and the inorganic compound of Comparative Example 2 (high-temperature calcined), while Figure 11 shows side-by-side FT-IR spectra of the inorganic compound of Example 2 calcined by short-term ultraviolet irradiation and the inorganic compound of Comparative Example 1 calcined by low-temperature heating in an atmospheric furnace.
[0109] Furthermore, based on the FT-IR spectrum, the inorganic compounds of Examples 1 and 2 and Comparative Examples 1 and 2 were evaluated as to whether the reaction was complete or not. The results are shown in Table 1.
[0110] In addition, FIG. 12 shows a comparison result between the hardness of the inorganic compound of Example 2, which was fired by short-time ultraviolet irradiation, and the hardness of the inorganic compound of Comparative Example 1, which was fired in a low-temperature atmospheric furnace.
[0111] [Table 1]
[0112] (4) Discussion The production of inorganic compounds (silicic acid compounds) by the sol-gel method using silicon alkoxide as a starting material is completed when the hydroxyl group species of Si-OH produced by the hydrolysis reaction of silicon alkoxide undergoes dehydration condensation through a polycondensation reaction to produce Si-O-Si bonds.
[0113] Therefore, even if it can be confirmed that inorganic compounds in the calcined samples have Si-O bonds, and thus that silicate compounds have been produced, if Si-OH (hydroxyl groups) remain, this means that the reaction has not yet reached completion.
[0114] In the FT-IR spectrum, the Si-O stretching vibration peak is at a wavelength of 1000 cm -1A peak appears in this region in the spectral shapes of the inorganic compounds of Examples 1 and 2 and Comparative Examples 1 and 2, and it has been confirmed that the inorganic compounds obtained by both firing methods have Si-O bonds, i.e., are silicic acid compounds.
[0115] However, in the inorganic compound of Comparative Example 1, which was fired in a low-temperature atmospheric furnace, Si-OH stretching vibrations appeared in the spectral shape, confirming that Si-OH (hydroxyl group) still remained and therefore the reaction was incomplete (see Figure 11).
[0116] On the other hand, in the inorganic compounds of Examples 1 and 2 that were calcined by ultraviolet irradiation, the FT-IR spectrum shape of none of the samples showed any characteristic Si-OH stretching vibration (see Figures 8, 9, and 11), and it was confirmed that the remaining Si-OH (hydroxyl group) was below the lower detection limit by the FT-IR method, and therefore the reaction was nearly complete.
[0117] In order to achieve completion of such a reaction by firing in an atmospheric furnace, it is necessary to fire at a high temperature for a relatively long period of time, as in Comparative Example 2, which may cause dimensional changes in the heat-insulated object.
[0118] In contrast, when baking is performed by irradiating with light with wavelengths in the ultraviolet range as in the present invention, it is possible to proceed (to completion) the polycondensation reaction to a state comparable to that of Comparative Example 2, in which baking is performed for a relatively long time at a high temperature that can cause dimensional changes in the heat-shielded object, without baking at such high temperatures, even when baking is performed by irradiating with ultraviolet rays for a relatively short time.
[0119] As shown in Figure 12, the hardness of the inorganic compound in Comparative Example 1, which was fired using a low-temperature atmospheric furnace, was approximately 30 in HV, while the hardness of the inorganic compound in Example 2, which was fired by short-term ultraviolet irradiation, was approximately 65 in HV, more than twice as hard.
[0120] From the above results, it has been confirmed that by sintering the inorganic compound layer 10 by irradiating it with light of a wavelength of 500 nm or less, preferably in the ultraviolet range (200 to 400 nm), it is possible to produce an inorganic compound in which the polycondensation reaction has been completed, and therefore an inorganic compound with greater hardness, and that sintering can be carried out in a shorter time than known sintering methods using an atmospheric furnace, thereby preventing the occurrence of thermal effects (dimensional changes, etc.) on the parts to be heat-shielded, and producing an inorganic compound with greater hardness in a shorter time.
[0121] [pH adjustment effect confirmation test] (1) Purpose of the study It is confirmed that pH adjustment of alkoxide paint is effective in increasing the hardness of inorganic compounds after firing.
[0122] (2) Test method An alkoxide paint (containing mica as scaly inorganic particles) was prepared using silicon alkoxide as the starting material, and an unadjusted paint (pH 9) and an adjusted paint (pH 10) were prepared by adding amine to this paint as a pH adjuster.
[0123] In this test example, m-xylylenediamine was used as the amine.
[0124] The coating films obtained by applying the unadjusted paint and the adjusted paint were pre-baked to harden them to a pencil hardness of 3H, and then differential thermogravimetric analysis (TG) was performed to measure the thermal changes of each sample, in which thermogravimetry (TG) is performed to continuously measure the weight change while the sample is heated at a constant rate, and differential thermal analysis (DTA) is performed to measure the change in temperature difference between the two when the sample is heated together with a reference substance.
[0125] In addition, samples similar to those used in differential thermogravimetry analysis (TG-DTA) were calcined using a low-temperature atmospheric furnace (under the same conditions as in Comparative Example 1 above) and by ultraviolet irradiation (under the same conditions as in Example 2 above), and the hardness of the resulting inorganic compounds was measured.
[0126] Furthermore, the raw material liquid was adjusted to pH 9, pH 9.5, pH 9.8, and pH 10 with the amine addition amount set to 0 mass%, 1 mass%, 2 mass%, 3 mass%, and 5 mass%, and pre-dried samples were obtained in the same manner as described above. These were then calcined by ultraviolet irradiation (under the same conditions as in Example 2 above), and the hardness of the obtained inorganic compound was measured.
[0127] (3) Test results Figure 13 shows the TG-DTA results for a sample obtained using an untreated raw material solution (pH 9) that had not been subjected to pH adjustment, and Figure 14 shows the TG-DTA results for a sample obtained using a treated raw material solution (pH 10) whose pH had been adjusted by adding an amine.
[0128] FIG. 15 shows the change in hardness with and without pH adjustment when firing in an atmospheric furnace, and FIG. 16 shows the change in hardness with and without pH adjustment when firing by ultraviolet irradiation.
[0129] Furthermore, the change in hardness of inorganic compounds with respect to the change in pH (change in the amount of amine added) is shown in FIG.
[0130] (4) Discussion (4-1) Relationship with hydrolysis reaction As a result of differential thermogravimetry analysis (TG-DTA), in the sample made from unadjusted paint (pH 9), a heat generation peak was observed, which was thought to be due to heat generated by thermal decomposition of unreacted silicon alkoxide that had remained unhydrolyzed, as shown in Figure 13. In contrast, in the sample made using adjusted paint (pH 10), the temperature difference with the reference substance remained almost flat, and no heat generation peak was observed, as shown in Figure 14.
[0131] From this, it is considered that adjusting the pH of the raw material liquid from 9 to 10 promoted the hydrolysis of the raw material liquid.
[0132] As shown in FIG. 4, the hydrolysis reaction rate of an alkoxide relative to changes in pH is lowest at neutral (pH 7) and increases as the degree of alkalinity or acidity increases.
[0133] Therefore, for silicon alkoxides that originally have a pH of 9, the hydrolysis reaction rate can be increased by adjusting the pH to more alkaline than 9, for example to pH 9.5 or higher, thereby making it possible to shorten the pre-baking time and the main baking time.
[0134] Furthermore, as shown in Figure 4, the hydrolysis reaction rate of alkoxides improves not only when it is shifted to the alkaline side, but also when it is shifted to the acidic side. Therefore, it is reasonably presumed that the hydrolysis reaction rate can also be improved by, for example, adding an acid such as phthalic anhydride as a pH adjuster to shift the rate to the acidic side, for example to a pH of 4 or less, thereby making it possible to shorten the pre-baking time and baking time.
[0135] (4-2) Relationship with hardness of inorganic compounds As shown in Figure 15, when firing was performed in an atmospheric furnace, adjusting the pH of the paint from pH 9 to pH 10 not only did not result in an increase in hardness, but it was confirmed that the hardness actually decreased.
[0136] On the other hand, in the example where baking was performed by ultraviolet irradiation, as shown in FIG. 16, it was confirmed that the hardness of the inorganic compound layer after baking was significantly increased by adjusting the pH.
[0137] This confirmed the effectiveness of combining baking by ultraviolet irradiation with pH adjustment of the raw material solution in increasing the hardness of the inorganic compound layer.
[0138] Furthermore, as shown in Figure 17, such an increase in hardness was obtained by simply adding 1 mass% amine, and it was confirmed that a significant increase in hardness could be obtained by simply shifting the pH slightly toward the alkaline side (adjusting the pH to 9.5) compared to the pH before adjustment.
[0139] [Test using a mixture of tetrafunctional and trifunctional alkoxides] (1) Purpose of the study It is confirmed that by adjusting the number of functional groups of the alkoxide, a decrease in Young's modulus can be obtained, which can contribute to preventing the occurrence of cracks.
[0140] In addition, by combining the amount of pH adjuster added and the adjustment of the number of functional groups, a combination of conditions is sought that can satisfy the conflicting demands of lowering Young's modulus while maintaining the effect of increasing hardness by adjusting the pH.
[0141] (2) Experimental Method The Young's modulus of the inorganic compound layer was measured using an alkoxide paint (containing mica as scale-like inorganic particles) manufactured using a starting material in which a trifunctional alkoxide was added to a tetrafunctional alkoxide to achieve a trifunctional alkoxide content of 17 mass%, 33 mass%, and 50 mass%.
[0142] In addition, starting materials were prepared by adding alkoxides of three functional groups at 0 mass%, 17 mass%, 33 mass%, and 50 mass%, and the change in hardness (HV) of the inorganic compounds obtained was measured when the amount of amine added, a pH adjuster, was varied between 0 and 5 mass%.
[0143] (3) Test results FIG. 18 shows the results of measuring the change in Young's modulus with respect to the amount of trifunctional alkoxide added.
[0144] Figure 19 shows the results of measuring the change in hardness (HV) with respect to the amount of amine added for each inorganic compound layer formed using an alkoxide paint that had alkoxides containing 0 mass%, 17 mass%, 33 mass%, and 50 mass% of the three functional groups as starting materials.
[0145] An example of the characteristics obtained in an inorganic compound layer that was baked by irradiation with ultraviolet light and the composition of a material that exhibited said characteristics [a combination of the amount of amine added (pH adjustment) and the amount of three functional groups added] is shown in Table 2 below.
[0146] [Table 2]
[0147] (4) Discussion As shown in Figure 18, the Young's modulus of the inorganic compound using an alkoxide containing 100% by mass of 4 functional groups (0% by mass of 3 functional groups) as the starting material was approximately 25 GPa, whereas it was confirmed that the Young's modulus of all of the compounds to which 3 functional groups were added was significantly lower than the target value of 20 GPa.
[0148] This confirmed that the addition of trifunctional alkoxides was effective in lowering the Young's modulus, which is expected to prevent cracks from occurring.
[0149] Furthermore, as shown in Figure 19 and Table 2 above, among the samples with trifunctional alkoxide added, the sample with 33 mass% trifunctional addition showed the highest hardness. In particular, at 2 mass% amine addition, where the hardness peaks, the hardness is close to that of the sample with 100 mass% tetrafunctional alkoxide, although it is slightly lower. Compared to the sample with 100 mass% tetrafunctional alkoxide, there is a significant decrease in Young's modulus, while the hardness remains high, demonstrating an unexpected effect of satisfying the conflicting requirements.
[0150] [Fatigue and durability tests] (1) Purpose of the experiment The durability of the heat insulating film of the present invention, which includes an inorganic compound layer and is formed based on the above test results, is confirmed when the film is applied to the top surface of an engine piston.
[0151] (2) Test method (2-1) Target Working Example The top surface of an aluminum alloy piston for an engine is coated with a density of 2.5 g / cm by anodizing in a sulfuric acid bath. 3 An anodized aluminum layer consisting of an oxide film was formed to a thickness of 40 μm.
[0152] On this anodized aluminum layer, an inorganic compound layer containing 40 mass % mica as scaly inorganic particles was formed to a thickness of 25 μm, forming a thermal barrier film having a two-layer structure of an anodized aluminum layer and an inorganic compound layer.
[0153] The inorganic compound layer was formed by the sol-gel method using tetrapropoxysilane as the starting material. Tetrapropoxysilane and water were mixed using a solvent to obtain a raw material liquid, and then scale-like inorganic particles made of the mica mentioned above were dispersed in the raw material liquid to create a paint. This paint was then applied to the anodized layer formed on the top surface of the piston to form a coating, and the piston with the coating formed on it was then pre-baked and baked to form the coating.
[0154] The firing process is carried out using ultraviolet light (light source heat capacity 2-4 kW, peak illuminance 700-1800 mW / cm 2 ) was irradiated.
[0155] The paint compositions used were the one that showed the greatest hardness in the previous test examples (amine 2% by weight, trifunctional groups 0% by weight), the one that showed a good overall balance of hardness and Young's modulus (amine 2% by weight, trifunctional groups 33% by weight), and the one that showed the greatest flexibility (lowest Young's modulus) (amine 5% by weight, trifunctional groups 50% by weight).
[0156] Comparative Example As a comparative example, a paint using a tetrafunctional alkoxide as the starting material (without the addition of amines or trifunctional groups) was prepared, which was baked in a low-temperature atmospheric furnace instead of being baked by ultraviolet irradiation as in the above examples.
[0157] (2-2) Single unit fatigue test (hydropulse test) A single-unit fatigue test was carried out on the pistons of the embodiment and comparative example using a hydropulse test device shown in FIG.
[0158] The test was conducted by placing a piston with a connecting rod fixture attached inside the cylinder fixture, which was then housed inside the casing, and applying pressure equivalent to the inertia force of the piston from the connecting rod fixture side, while periodically applying a pressure equivalent to the maximum combustion pressure (Pmax) to silicone oil filled in the part corresponding to the combustion chamber.
[0159] The test conditions were a pressure of 8 MPa equivalent to the maximum combustion pressure (Pmax) at a frequency of 30 Hz. The test temperature was 250°C and the number of repetitions was 1×10 7 It is.
[0160] (2-3) Durability test (actual engine test) The pistons of the example and the comparative example were respectively mounted in an engine and subjected to a durability test.
[0161] The engine is a 2.5-liter, in-line 4-cylinder, naturally aspirated mass-produced engine with a top speed of 6000 min. -1 The engine was operated at full load for 60 hours. The maximum combustion pressure in the combustion chamber was 7 MPa.
[0162] (3) Test results and considerations (3-1) Results of unit fatigue test (hydropulse test) As a result of a single unit fatigue test (hydropulse test), in the piston of the comparative example, cracks were generated in the inorganic compound layer parallel to the painted surface, and intralaminar peeling occurred in the inorganic compound layer due to stretching.
[0163] Furthermore, in the comparative example piston, fracture was confirmed to have occurred near the interface between the anodized aluminum layer and the inorganic compound layer.
[0164] It is believed that this type of destruction near the interface between the inorganic compound layer and the anodized layer occurs when gas in tiny holes, called "pores," in the anodized layer expands due to the test environment temperature, destroying the brittle inorganic compound above the pores.
[0165] In contrast, in the pistons of the embodiments in which a heat-shielding film was formed using the method of the present invention, peeling and damage to the inorganic compound layer was reduced by more than 50% compared to the comparative examples, regardless of the paint composition, and no large rupture marks were observed at the interface between the anodized layer and the inorganic compound layer.
[0166] It is believed that this result is due to the fact that the hardness of the inorganic compound layer formed by the method of the present invention is increased compared to that of the comparative example, thereby suppressing damage at the interface between the anodized layer and the inorganic compound layer due to the expansion of the gas in the pores as described above.
[0167] In this way, it was confirmed that the heat-shielding film applied to the piston of the embodiment had significantly improved fatigue strength compared to the heat-shielding film applied to the piston of the comparison example, and the effectiveness of sintering the inorganic compound layer by ultraviolet light irradiation was confirmed.
[0168] (3-2) Durability test (actual engine test) results As a result of the aforementioned durability tests conducted by installing the pistons of the embodiment and comparative example in an engine, peeling occurred within the inorganic compound layer in the piston of the comparative example, and cracks occurred and propagated within the layer, and the propagated cracks joined together, causing ruptures and defects within the layer.
[0169] As a result, in the heat insulating film formed on the piston of the comparative example, the film thickness after the test was reduced to 20 to 30% of the film thickness before the test (100%).
[0170] In contrast, in the pistons of the embodiments equipped with a heat-shielding film formed by the method of the present invention, it was confirmed that the rate of crack occurrence in the inorganic compound layer was reduced by 50 to 70% compared to the comparative examples, regardless of the composition of the paint used to form the inorganic compound layer.
[0171] Moreover, in the pistons of the examples, the thickness of the heat insulating film did not change before and after the test, and the film thickness before the test was maintained even after the test.
[0172] It is believed that the maintenance of such a film thickness is an effect obtained by increasing the hardness of the inorganic compound layer by forming it using the method of the present invention.
[0173] In other words, although cracks did occur in the inorganic compound layer in the piston of the embodiment, it is presumed that the increased hardness of the inorganic compound layer prevented the propagation of such cracks and the bonding of the cracks that accompanies their propagation, thereby preventing the occurrence of ruptures or defects within the layer.
[0174] Therefore, the results of the durability test (implementation test) also confirmed the effectiveness of the present invention, in which the inorganic compound layer is baked by irradiation with ultraviolet rays. [Explanation of symbols]
[0175] 1. Heat shielding film 2. Parts to be heat-shielded (pistons) 10 Inorganic compound layer 11 Inorganic compounds 12 Scaly inorganic particles 20 Anodized Layer
Claims
1. In a heat shield part for a vehicle, at least a part of the surface of a heat shielding target part is covered with a heat shielding film, The heat-shielding film includes at least an inorganic compound layer formed by dispersing one or more types of scale-like inorganic particles selected from the group consisting of mica, talc, and wollastonite in an inorganic compound formed from an alkoxide, the inorganic compound layer has a Vickers hardness (HV) of 50 to 100; A heat shielding part for a vehicle, the part to be heat shielded maintaining its outer dimensions before the heat shielding film was formed.
2. 2. The heat shield part for a vehicle according to claim 1, wherein the inorganic compound layer has a Young's modulus of 12 to 25 GPa.
3. 3. The heat shielding part for a vehicle according to claim 1, wherein the heat shielding film comprises an anodized aluminum layer below the inorganic compound layer.
4. 4. The heat shield component for a vehicle according to claim 3, wherein the anodized aluminum layer is a sulfate anodized aluminum layer.
5. The heat shield part for a vehicle according to any one of claims 1 to 4, wherein the inorganic compound layer has a thickness of 10 to 200 µm.
6. The heat shield part for a vehicle according to any one of claims 1 to 5, wherein the heat shield film has a thickness of 10 to 400 µm.
7. 7. The heat shield part for a vehicle according to claim 1, wherein the alkoxide is a mixture of 30 to 100% by mass of an alkoxide having tetrafunctional groups and 0 to 70% by mass of an alkoxide having difunctional groups or trifunctional groups.
8. 8. The heat shield part for a vehicle according to claim 1, wherein the part to be heat shielded is a piston for an engine.
9. A heat shielding film formed on at least a part of a surface of a heat shielding target part and constituting a heat shielding target part for a vehicle together with the heat shielding target part, A heat insulating film formed on the surface of the part to be heat-insulated, the heat insulating film comprising at least an inorganic compound layer having a Vickers hardness (HV) of 50 to 100, the inorganic compound being formed from an alkoxide and having one or more types of scale-like inorganic particles selected from the group consisting of mica, talc, and wollastonite dispersed therein, and the part maintaining its external dimensions prior to the film formation.
10. The thermal barrier film according to claim 9 , further comprising an anodized aluminum layer below the inorganic compound layer.
11. The heat shielding film according to claim 10, wherein the thickness of the anodized aluminum layer is 10 to 200 μm.
12. The heat shielding film according to any one of claims 9 to 11, wherein the inorganic compound layer has a thickness of 10 to 200 µm.
13. A method for manufacturing a heat shielding part for a vehicle, comprising covering at least a part of a surface of a heat shielding part with a heat shielding film, the heat shielding film includes at least an inorganic compound layer in which one or more types of scale-like inorganic particles selected from the group consisting of mica, talc, and wollastonite are dispersed; The inorganic compound layer is a paint production process for producing a paint comprising an alkoxide solution in which the scaly inorganic particles are dispersed; A coating film forming process in which the paint is applied to the surface of the heat-shielding target part to form a coating film; The method for manufacturing a heat shielding part for a vehicle is characterized in that the coating film is formed through a baking process in which the coating film is baked to a Vickers hardness (HV) of 50 to 100 while suppressing a temperature rise of the heat shielding part by irradiation with light having a wavelength of 500 nm or less.
14. The method for manufacturing a heat shielding part for a vehicle according to claim 13, characterized in that the alkoxide is a mixture of 30 to 100 mass % of a tetrafunctional alkoxide and 0 to 70 mass % of a difunctional and / or trifunctional alkoxide.
15. The heat insulating film includes an anodized aluminum layer, 15. The method for manufacturing a heat shielding part for a vehicle according to claim 13, wherein the coating film forming step is carried out on a surface of the heat shielding target part made of aluminum or an aluminum alloy on which an anodized aluminum layer is formed.
16. The method for manufacturing a heat shield part for a vehicle according to claim 15, wherein the anodized aluminum layer is formed by anodizing using a sulfuric acid bath.
17. The method for manufacturing a heat shield part for a vehicle according to any one of claims 13 to 16, wherein the part to be heat shielded is a piston for an engine.
Citation Information
Patent Citations
Oil cooler for motorcycle
JP1985067712A
Linking of magnetic head to mounting plate
JP1988039118A
Member composing combustion chamber of internal combustion engine and its manufacture
JP1996105352A
Heat insulation structure of engine combustion chamber component, and method for manufacturing the same
JP2014040816A
Anode oxidation treatment method and internal combustion engine structure
JP2015193915A
